A Novel Compressive Optical Encryption via Single-Pixel Imaging - Chenggong Zhang; Bennian Han; Wenqi He; Xiang Peng; Chen Xu (IEEE Photonics Journal)
A novel compressive optical cryptosystem based on single-pixel imaging is proposed. By using random sparse sampling in the encryption process, the plaintext is encrypted and compressed into a noise-like intensity sequence. As a result, the ciphertext is much less than the plaintext in volume. For decryption, a convex optimization algorithm is employed to reconstruct the plaintext with the help of the correct key based on the compressive sensing theory. Computer simulations and optical experiments are conducted and a series of results verify the validity and feasibility of the proposed method.